2024
DOI: 10.22270/jddt.v14i3.6490
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Stigma and Mental Health Disorders in People Living with HIV/AIDS

Pallav Dave

Abstract: Stigma remains a significant challenge for people living with HIV/AIDS(PLWHA) despite the advances that have been made in HIV care and treatment. It is known to affect health care outcomes including care seeking habits and medication adherence. In addition to contributing to poor health outcomes, stigma is known to increase the risk of developing mental health disorders. Various researchers have found a correlation between stigma and mental health disorders including depression, anxiety, mental distress, stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Additionally, Callistemon citrinus syn. Callistemon lanceolatus shown anti-bacterial, anti-helicobacter pylori, hypoglycemic, spasmolytic, antioxidant, and hepatoprotective properties 13 .…”
Section: Calcium Channel Blocking Actionmentioning
confidence: 99%
“…Additionally, Callistemon citrinus syn. Callistemon lanceolatus shown anti-bacterial, anti-helicobacter pylori, hypoglycemic, spasmolytic, antioxidant, and hepatoprotective properties 13 .…”
Section: Calcium Channel Blocking Actionmentioning
confidence: 99%
“…In addition, patients often create techniques to manage freezing episodes. These strategies involve following commands like marching, stepping over objects (such as a walking stick or cracks in the floor), walking to the rhythm of music or a beat, and shifting body weight [34][35][36] .…”
Section: ❖ Tremormentioning
confidence: 99%
“…According to Deters and Mehl, posting Facebook status updates decreased loneliness. 7 It decreased loneliness because it made people feel more connected and in touch with their friends on a daily basis. Social media was also seen as a tool of social support for sexual minority and heterosexual youth.…”
Section: Reasons Why Social Media Increases the Risk Of Mental Healthmentioning
confidence: 99%
“…Doubleedged sword in the sense that it allows young people to express their feelings and receive social support, and also contributes to an increased risk of having mental health issues and other psychological problems. 5,6,7,8,9,10 Research has also shown that individuals who live with different mental disorders use social platforms more than the general population. 11,12 The high use of social platforms in this population could be attributed to a number of factors including as a platform to seek information, as a mechanism to give and receive social support, or as a mechanism to cope.…”
Section: Introductionmentioning
confidence: 99%